Pengaruh Kualitas Konten Influenser terhadap Minat Beli Konsumen di Salon Floom Beauty Longue - Nauli, Roma Dona; Vera, Vety; Yuneri, Winda (Pakis Journal Institute, 2025)
This research aims to help increase the marketing of Floom Beauty Longue Salons through social media content and increase public interest in treatments. In the current digital era, marketing through influencers has become an effective strategy in reaching potential customers, especially in the beauty industry. The quality of content which includes visual aspects, information, and influencer credibility are important factors in building trust and attracting consumer interest. This type of research is descriptive qualitative research which aims to describe the phenomena that occur and provide a clearer understanding of how the quality of influencer content can influence consumers' decisions to make purchases at the salon. The results of this research are that influencers have a significant influence on consumer purchasing interest. Therefore, Floom Beauty Lounge Salon is advised to collaborate with influencers who have high credibility and ensure that the content produced has good aesthetic and informative value. Additionally, salons can increase engagement with customers through social media to maintain customer loyalty.